Importance of the psychosocial environment in epidemiologic studies - Marmot, Michael (Scandinavian Journal of Work, Environment & Health, 1999)
It has been common for the starting point of occupational health studies to be the disease risks associated with particular occupations. The research effort then focuses on features of the work environment that might be exposures for the particular disease. The starting point of this paper has been different; it is the inverse social gradient in morbidity and mortality observed in all industrialized (and nonindustrialized) countries. In Great Britain, it has been usual for the socioeconomic classification to be based on occupation. This usage raises the question of how much of the social gradient in disease is related to the circumstances under which people work, and how much to living circumstances, acting through the life course. This paper illustrates how attention to psychosocial factors in the workplace and outside have the potential to reduce the burden of ill health for working people and to diminish the social gradient in morbidity and mortality.
Keywords: control; early life; morbidity; mortality; relative deprivation; social inequality; work environment